Invigorasi Benih Cabai Rawit Cv. Hiyung (Capsicum frutescens L.) Menggunakan Larutan Bawang Merah - Amalia, Hilma; Suparto, Hairu; Saputra, Riza Adrianoor; Nugraha, Muhammad Imam; Nurlaila, Nurlaila (Sandalwood Journal Of Agribusiness And Agrotechnology, 2025)
Decline in physiological seed quality during storage can significantly reduce viability and vigor, including in Hiyung cayenne pepper, a superior local variety from South Kalimantan. One potential solution is the invigoration technique, which involves treating seeds with certain solutions to restore their quality. This study aimed to examine the effect of shallot extract as a natural invigoration agent and to determine the best concentration to improve the viability and vigor of Hiyung cayenne pepper seeds that have exceeded their storage period. The research was conducted at Seed Control and Certification Center for Food Crops and Horticulture (BPSBTPH) Banjarbaru from July to August 2024 using a completely randomized design with one factor: four solution concentrations (0%, 10%, 15%, 20%) and five replications. Observed parameters included maximum growth potential, germination rate, vigor index, uniformity, and growth rate. The results showed that shallot extract had a significant effect on germination rate and growth rate, but no significant effect on maximum growth potential, vigor index, and uniformity. Application of 10% shallot extract improved seed viability, while 20% concentration enhanced the vigor of Hiyung cayenne pepper seeds that had exceeded their storage period.